Analysis of factors influencing spatiotemporal differentiation of the NDVI in the upper and middle reaches of the Yellow River from 2000 to 2020 - Gao, Siqi; Dong, Guotao; Jiang, Xiaohui; Nie, Tong; Guo, Xinwei (Frontiers in Environmental Science, 2023)
Surface vegetation represents a link between the atmosphere, water, and human society. The quality of the ecological environment in the upper and middle reaches of the Yellow River (UMRYR) has a direct impact on the downstream basin. Few studies of vegetation changes in the UMRYR have been conducted. Therefore, we used the coefficient of variation and linear regression analyses to investigate spatiotemporal variations in the normalized difference vegetation index (NDVI) and we used the geographical detector model (GDM) to determine the spatial heterogeneity of the NDVI and its driving factors, and investigated the factors driving the spatial distribution of the NDVI in different climatic zones and vegetation types. The results showed that the NDVI in the UMRYR was high during the study period. The NDVI was distributed in a spatially heterogeneous manner, and the NDVI decreased from the southeast to northwest. The NDVI with severe degradation in the southeast, mild degradation in the northwest and the Yellow River source region, and substantial vegetation recovery in the central basin. Precipitation and vegetation types drove the spatial distribution of the NDVI. The influence of natural factors was larger than that of anthropogenic factors, but the interactions between the natural and anthropogenic factors exhibited non-linear and bivariate enhancements. Inter-annual variations in precipitation were the main natural factors influencing inter-annual NDVI variations, while precipitation and anthropogenic ecological restoration projects jointly drove NDVI changes in the UMRYR. This study provides a better understanding of the current status and mechanisms driving vegetation restoration in the UMRYR.